2011
DOI: 10.1371/journal.pone.0029126
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of Type I Interferon Activity and TNF-Alpha Levels in Serum with Sarcoidosis Manifestations and Ancestry

Abstract: BackgroundBoth type I interferon (IFN), also known as IFN-α and tumor necrosis factor alpha (TNF-α) have been implicated in the pathogenesis of sarcoidosis. We investigated serum levels of these cytokines in a large multi-ancestral sarcoidosis population to determine correlations between cytokine levels and disease phenotypes.MethodsWe studied serum samples from 98 patients with sarcoidosis, including 71 patients of African-American ancestry and 27 patients of European-American ancestry. Serum type I IFN was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 38 publications
0
16
0
1
Order By: Relevance
“…In the study showing serum levels of TNF-α and IFN-α in sarocoidosis, significant differences in cytokine levels were found between sarcoidosis patients of different ancestral Sarcoidosis 36 backgrounds [9]. In this study, African-Americans had higher TNF-α levels than EuropeanAmerican patients or matched controls, and patients with neurologic disease had significantly higher TNF-α than patients lacking this manifestation.…”
Section: Cross-regulation Between Type I Ifn and Tnf-αmentioning
confidence: 48%
See 3 more Smart Citations
“…In the study showing serum levels of TNF-α and IFN-α in sarocoidosis, significant differences in cytokine levels were found between sarcoidosis patients of different ancestral Sarcoidosis 36 backgrounds [9]. In this study, African-Americans had higher TNF-α levels than EuropeanAmerican patients or matched controls, and patients with neurologic disease had significantly higher TNF-α than patients lacking this manifestation.…”
Section: Cross-regulation Between Type I Ifn and Tnf-αmentioning
confidence: 48%
“…In this study, African-Americans had higher TNF-α levels than EuropeanAmerican patients or matched controls, and patients with neurologic disease had significantly higher TNF-α than patients lacking this manifestation. In a European-American population, serum type I IFN activity was higher in sarcoidosis cases as compared to matched controls, and patients with extra-pulmonary disease represented a high serum IFN group [9]. This study demonstrated ancestral and subphenotype correlations with serum cytokine levels in patients with sarcoidosis.…”
Section: Cross-regulation Between Type I Ifn and Tnf-αmentioning
confidence: 51%
See 2 more Smart Citations
“…Numerous studies have confirmed high TNF-α production in cases with sarcoidosis, and have shown an important role of TNF-α in granuloma formation (37)(38)(39)(40)(41). Moreover, mononuclear phagocytes, such as mature macrophages, are responsible for the TNF-α secretion in patients with sarcoidosis (42).…”
Section: Tnf-αmentioning
confidence: 97%